The answer is in the room : how effective schools scale up student success - Blankstein, Alan M. (Thousand Oaks : Corwin Press, a joint publication with the HOPE Foundation, 2011)
'Best-selling author Alan Blankstein shares the results of his research with top educational experts and describes a five-step process of finding and scaling excellent practices within learning communities'-- Provided by publisher.
'Best-selling author Alan Blankstein shares the results of his research with high-achieving schools and districts, providing insights, a process, and tools for identifying excellence and putting their methods into practice. He believes that we already know how to educate students, and good methodology for teaching, leading or organizing a highly effective school can be identified and scaled across the learning community. Blankstein shows how to tap into our collective wisdom and answers that already exist, and shares top educators' -Examples of what is working -Methodologies for achieving success (the CREATE process) -Techniques for giving all teachers necessary feedback -Solutions to today's educational challenges Policy makers, practitioners, parents, and community leaders will find a new approach to assuring success for all students'-- Provided by publisher.
Machine generated contents note: PrefaceAcknowledgmentsAbout the AuthorDedicationFigures and Tools to Help Answer the Questions in the Room1. Why We Can't Wait to Scale Student Success! The Power of Positive Deviance Saves Millions of Children in Vietnam Applying Positive Deviance to Education Good News for Scaling Student Success About This Book and Chapter Some Common Core Principles of Networking and PD Challenges to Scaling Success in US Education The Moral and Economic Imperative for Change is Now What Works, What Doesn't, What's Next? The Big Question References2. A Process to CREATE Sustained Student Success A Movement is Born in U.S. Education and Exported to Other Nations The Catalyst to Change The CREATE Process The Advantages of the CREATE Process The Big Question References3. The Courage to Commit to the Work Defining Courage Commitment: A Pillar of Courage Building a Collective Commitment to Scale Up Student Success 7 Tools for Constructing a Large-Scale Community Commitment Cultivating the Community: Qualities of the Courageous Leader The Big Question References4. Resources are in the Room The Most Valuable Resource: Focused Commitment Over Time The Second Major Resource: Patience and Urgency Third Major Resource: Steering Committee How to Get TIME to Collaborate Getting Down to the Details The Big Question References5. Taking Stock of Excellence in the Room Is there Excellence or Positive Deviance to be Found? Defining Excellence is Done Twice by the Lead Teams Developing a Community to Question the Answer: Language, Purpose and Norms Improving Instructional Practice: Change the Methods and You Will Change the Outcomes Change the Methods and You Will Change the Outcomes The Big Question References6. An Action Plan for Engaging the Entire Learning Community Developing a Common Language for the Action Plan Key Challenges to Address in the Action Plan Reentry Plans to Engage the Larger School Community, Build Trust and Transparency Developing SMART Goals That the School Community Wants to Achieve Successful Implementation of SMART Goals Identifying and Assessing Excellence Next Steps The Big Question References7. Transference of Knowledge and Skills Throughout the Learning Community Transferring Knowledge and Skills within the School Transferring Knowledge and Skills Through-out the District What Are Tuning Protocols? The Big Question References 8. Embedding the New Learning in the Culture for Sustainability Three Pillars of Embedding the Process in the School Culture The Big Question ReferencesTools to Help Answer the Questions in the RoomTool A: Writing an Instructional SMART Goal WorksheetTool B: Strategies for Making TimeTool C: Agreement of PURPOSE WorksheetTool D: Creating Group Norms: Facilitator Guide ExampleTool E: An Example Participant Handout for Creating Group NormsTool F: Steps of'Instructional Learning Walks'Tool G: Indicators of Quality Instructional Learning Walks Observation SheetIndex.
Includes bibliographical references (p. 111-113) and index.
Keywords: School improvement programs; Educational leadership; EDUCATION / Leadership